Kompetisi Bisnis Konvensional Terhadap Bisnis Online Pada Media Sosial Di Kecamatan Klirong Kebumen - Farkhan Fuady; Alfiana Zahwa Nur Rokhmat (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Technological advances make it easier for humans to carry out daily activities, especially in terms of doing business. Online business is the implementation of technological advances. So this research will explore conventional business strategies with online businesses. This study aims to determine the strengths and weaknesses of the two businesses. It also aims to find out the business strategy in maintaining its business. This study uses a qualitative approach. Data collection methods are interviews and observation. The data validity technique uses the Triangulation technique. The findings of this study prove that social media is used as a promotional medium for both conventional and online businesses. This study also proves that in order to maintain a conventional business in the midst of the rise of online business, shopping vouchers are given with applicable regulations.